Figure 25 from: Prous M, Liston A, Mutanen M (2021) Revision of the West Palaearctic Euura bergmanni and oligospila groups (Hymenoptera, Tenthredinidae). In: Proshchalykin MYu, Gokhman VE (Eds) Hymenoptera studies through space and time: A collection of papers dedicated to the 75th anniversary of Arkady S. Lelej. Journal of Hymenoptera Research 84: 187-269. https://doi.org/10.3897/jhr.84.68637 - Prous, Marko; Liston, Andrew; Mutanen, Marko (Zenodo, 2021)
Figure 25 Euura sylvestris larvae. A, B Finland 2018 Salix capreaC, D Finland 2019 Populus tremulaE Austria 2017 Salix hegetschweileri. Larvae of sylvestris found on Populus tremula in Finland in 2019 appear morphologically different from larvae on Salix, but based on genetics represent sylvestris.